A Diagnostic Panel for Acquired Immune-Mediated Polyneuropathies Based on the Expression of lncRNAs - Hussen, Bashdar Mahmud; Nicknafs, Fwad; Hidayat, Hazha Jamal; Sayad, Arezou; Ghafouri-Fard, Soudeh; Taheri, Mohammad (Frontiers in Immunology, 2021)
Long non-coding RNAs (lncRNAs) have been shown to alter immune responses, thus contributing in the pathobiology of autoimmune conditions. We investigated the expression levels of ANRIL, PICART1, MALAT1, CCAT1, CCAT2 and CCHE1 lncRNAs in acute and chronic acquired immune-mediated polyneuropathies (AIDP and CIDP). ANRIL, PICART1, MALAT1, CCAT1, CCAT2 and CCHE1 lncRNAs were significantly down-regulated in both AIDP and CIDP cases compared with unaffected individuals. Gender-based comparisons also verified such down-regulations in both male and female subjects compared with sex-matched unaffected controls for all lncRNAs. There was no significant difference in the expression of either lncRNA between AIDP cases and CIDP cases. While expression levels of ANRIL and PICART1 were significantly correlated in healthy subjects (r=0.86, P value=8.5E-16), similar analysis in AIDP and CIDP cases revealed no significant correlation. The most robust correlation among patients was detected between ANRIL and MALAT1 lncRNAs (r=0.59, P value=3.52E-6). ANRIL, MALAT1 and PICART1 had the diagnostic power of 0.96, 0.94 and 0.92 in distinguishing between CIDP cases and controls, respectively. Combination of all lncRNAs resulted in 0.95 diagnostic power with sensitivity of 0.85 and specificity of 0.96 for this purpose. Diagnostic power values of these lncRNAs in differentiation between AIDP cases and controls were 0.98, 0.95 and 0.93, respectively. The combinatorial diagnostic power reached 0.98 for differentiation between AIDP cases and controls. The 6-lncRNA panel could differentiate cases from controls with AUC, sensitivity and specificity values of 0.97, 0.90 and 0.96, respectively. Collectively, the lncRNA panel is suggested as a sensitive and specific diagnostic panel for acquired immune-mediated polyneuropathies.